Looking for answers? Westonci.ca is your go-to Q&A platform, offering quick, trustworthy responses from a community of experts. Experience the ease of finding accurate answers to your questions from a knowledgeable community of professionals. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
Sure! Let's convert the point-slope form equation [tex]\( y + 7 = \frac{2}{3}(x + 6) \)[/tex] into the slope-intercept form [tex]\( y = mx + b \)[/tex].
### Step-by-step solution:
1. Starting Equation:
[tex]\[ y + 7 = \frac{2}{3}(x + 6) \][/tex]
2. Distribute [tex]\(\frac{2}{3}\)[/tex] through the terms inside the parentheses:
[tex]\[ y + 7 = \frac{2}{3}x + \frac{2}{3} \cdot 6 \][/tex]
3. Multiply [tex]\(\frac{2}{3}\)[/tex] by 6:
[tex]\[ y + 7 = \frac{2}{3}x + 4 \][/tex]
4. Isolate [tex]\( y \)[/tex] by subtracting 7 from both sides:
[tex]\[ y = \frac{2}{3}x + 4 - 7 \][/tex]
5. Simplify the constants:
[tex]\[ y = \frac{2}{3}x - 3 \][/tex]
So, the slope-intercept form of the line is [tex]\( y = \frac{2}{3}x - 3 \)[/tex].
None of the options provided exactly match this equation, but the correct transformation of the given point-slope form is:
[tex]\[ y = \frac{2}{3}x - 3 \][/tex]
Therefore, the correct linear function that represents the line given by the point-slope equation [tex]\( y + 7 = \frac{2}{3}(x + 6) \)[/tex] is [tex]\( y = \frac{2}{3}x - 3 \)[/tex].
### Step-by-step solution:
1. Starting Equation:
[tex]\[ y + 7 = \frac{2}{3}(x + 6) \][/tex]
2. Distribute [tex]\(\frac{2}{3}\)[/tex] through the terms inside the parentheses:
[tex]\[ y + 7 = \frac{2}{3}x + \frac{2}{3} \cdot 6 \][/tex]
3. Multiply [tex]\(\frac{2}{3}\)[/tex] by 6:
[tex]\[ y + 7 = \frac{2}{3}x + 4 \][/tex]
4. Isolate [tex]\( y \)[/tex] by subtracting 7 from both sides:
[tex]\[ y = \frac{2}{3}x + 4 - 7 \][/tex]
5. Simplify the constants:
[tex]\[ y = \frac{2}{3}x - 3 \][/tex]
So, the slope-intercept form of the line is [tex]\( y = \frac{2}{3}x - 3 \)[/tex].
None of the options provided exactly match this equation, but the correct transformation of the given point-slope form is:
[tex]\[ y = \frac{2}{3}x - 3 \][/tex]
Therefore, the correct linear function that represents the line given by the point-slope equation [tex]\( y + 7 = \frac{2}{3}(x + 6) \)[/tex] is [tex]\( y = \frac{2}{3}x - 3 \)[/tex].
Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.